Lateral Thoracic Expansion for Jeune's Syndrome, Surgical Approach, and Technical Details - Lena, Federica; Piro, Liliana; Forlini, Valentina; Guerriero, Vittorio; Salvati, Pietro; Stagnaro, Nicola; Sacco, Oliviero; Torre, Michele; Mattioli, Girolamo (European Journal of Pediatric Surgery, 2022)
Introduction Jeune's syndrome, or asphyxiating thoracic dystrophy (ATD), is a rare autosomal recessive disorder characterized by skeletal dysplasia. Ribs are typically short and horizontal resulting—in lethal variant—in severe lung hypoplasia, progressive respiratory failure, and death. Lateral thoracic expansion (LTE) consists in staggered bilateral ribs osteotomy leading to chest expansion and lung development. Studies on LTE in ATD patients report encouraging data, but the rarity of ATD implies the lack of a standardized surgical path. The aim of this report is to present our experience with LTE, the technical modification we adopted, and patients' clinical outcome.Materials and Methods We retrospectively reviewed data of 11 LTE performed in 7 ATD patients with lethal variant. Information regarding pre- and postoperative clinical conditions and surgical details was collected. We adopted a single-stage or a two-stage approach based on patient clinical condition. Computed tomography (CT) scan was performed before and after surgery and lung volume was calculated.Results Five patients are alive, while two died in intensive care unit for other than respiratory cause (sepsis). Most patients experienced clinical improvement in terms of decreased respiratory infections rate, need for ventilation, and improved exercise tolerance. Postoperative CT scan demonstrated a median lung volume increase of 88%.Conclusion Mortality in ADT patients is high. However, LTE is a feasible and safe surgical approach, which could improve clinical conditions and survival rate. Survived patients showed postoperatively less oxygen requirement and improved clinical conditions.
Keywords: Jeune syndrome; asphyxiating thoracic dystrophy; lateral thoracic; expansion